Arrhythmic events in Brugada syndrome patients induced by fever - Roterberg, Gretje; El-Battrawy, Ibrahim; Veith, Michael; Liebe, Volker; Ansari, Uzair; Lang, Siegfried; Zhou, Xiao-Bo; Akın, Ibrahim; Borggrefe, Martin (Annals of noninvasive electrocardiology, 2020)
Introduction - The Brugada syndrome is associated with arrhythmic events, which may even lead to sudden cardiac death (SCD) as it causes arrhythmic events. A typical Brugada syndrome ECG type I can be triggered at fever situations.